Analisis Kemampuan Pemecahan Masalah Model Polya Materi Getaran, Gelombang, dan Bunyi Siswa SMP (UPEJ Unnes Physics Education Journal, 2020)
This study aims to determine the problem solving ability of the 9th grade students of Banyubiru 1 and 2 Junior High School in 2019/2020 in the material of wave, and sound. This is a survey research with descriptive qualitative analysis. The instrument used was an integrated test with Polya's model problem solving steps and interview guidelines. Test questions tested consists of 2 problem descriptions. The result shows that the ability of the students problem solving ability was still at the low level which is at 68.97%. Whereas, 90.32% of students' score are still below the minimum completeness criteria (KKM) in science subject. Students are able to achieve 2 indicators of Polya model problem solving namely understanding the problem and making plans. However, students have not yet been able to achieve the other 2 indicators, namely implementing the plan and checking again. The students found the difficulties in interpreting the Problem-type questions. They got difficult in understanding the intentions of the problem so that there is an error in compiling a strategy that results in students experiencing confusion in writing each answer. So training is needed in working on problem solving problems.